Perlindungan Hukum Penyewa terhadap Objek Hak Tanggungan yang Dibebani Hak Sewa - I Made Adi Saputra; A.A Sagung Laksmi Dewi; Luh Putu Suryani (Warmadewa Press, 2020)
As a business entity collecting money from the public and channeling it back to the public, the bank principle stipulates that collateral is required to provide credit to customers. The legal problem related to the bank studied in this study is that the object leased by the debtor to a third party is not with the knowledge of the creditor, whose final object is the executable mortgage. This study examines the legal protection for tenants related to executed mortgage objects and what the procedures for implementing the leased mortgage object are. This research was conducted using a normative legal research design with a legislation study approach. The legislative approach is realized by examining the problems (legal problems) that are being faced. The research results reveal that the legal protection for tenants related to the leased mortgage object can be seen from the regulation of Article 1576 BW, which stipulates that tenants can retain their rights on the grounds that the seller is not permitted to cancel the lease, but shall only defend their rights and the lessee with compensation for the end of the lease relationship. Legal protection demands that the lessee in relation to the lease appears because the lessee has neglected its performance as referred to in Article 1550 BW. The procedure for executing an object of mortgage bearing lease rights begins with filing an application and ends with execution. Requests for execution are made by submitting an application directly to the Head of the District Court by attaching a photocopy of court decisions (District Court decisions and / or Supreme Court decisions) which have permanent legal force. The party having the right to request execution is the party declared superior in the content of the court decision, either personally or through the lawyer, accompanied by a special power of attorney.